Advancing Data Linkage through Health Data Stewardship and Governance - Kelly, Maureen; Henderson, Tobi; Choy, Leslie; Fracassi, Jesse (International Journal of Population Data Science, 2026)
To maximize the value of Canada’s health system data, it must be timely, connected, accessible, comprehensive, relevant, contextualized and trusted. Currently, the Canadian health system operates as a series of data islands with varying degrees of governance, data content standardization and interconnectivity. To achieve a modern, connected health data ecosystem that enables cross-sectoral and cross-jurisdictional data linkage, a “team Canada” systems approach is needed. Central to this approach is the development and implementation of a pan-Canadian health data stewardship framework and governance model. The Framework outlines the conditions needed to share, link and use health data responsibly to benefit all Canadians, improve patient and population health and drive innovation. Public trust and engagement are a key component, ensuring stewardship reflects public values, needs and expectations. Other components cover considerations for advancing legislation, governance, data access and infrastructure to ensure the safe and ethical use of health data. The Governance Model establishes a national, strategic coordinating “nerve” centre for health data stewardship and supports shared decision-making and collaboration across jurisdictions. The model works to coordinate and align efforts to address data barriers and drive innovation, including in research, data linkage, and population data science. Together, the Framework and Governance Model aim to build the modern, connected, trusted health data ecosystem that Canada needs – one where health data follows patients across their care journey, is truly interoperable, and can be harnessed for system and research needs, improving care, equity, and outcomes for all Canadians.